The Impact of Hypertension Onset Age on the Risk of Cardiovascular Diseases and Mortality: Two 10-Year Retrospective Cohort Studies in the United Kingdom and Hong Kong - Ivy Lynn Mak; Boyuan Wang; Kiki Sze Nga Liu; Edmond Pui Hang Choi; Cindy Lo Kuen Lam; Eric Yuk Fai Wan (Journal of Primary Care & Community Health)
Introduction: This study examines the association between the age of hypertension onset and the risks of cardiovascular diseases (CVD) and mortality. Methods: Two retrospective cohort studies were conducted using electronic medical records from public healthcare systems in the UK and Hong Kong (HK). Adults (≥18 years) who attended public health services between January 1, 2008 and December 31, 2013 were included in the study. Patients diagnosed with CVD before baseline or who transferred out of practice before baseline in the UK cohort were excluded. Hypertension onset was defined as a diagnosis of hypertension (≥140/90 mmHg) or the prescription of anti-hypertensive medication. Patients were categorized based on hypertension onset and divided into 6 age groups based on onset age. Propensity score fine stratification weights were applied to ensure balance between groups. Multivariable Cox proportional hazards regression a was used to assess risks of CVD, cardiovascular mortality, and deaths. Results: The UK cohort included 481 791 new-onset hypertension patients and 3 893 134 controls, while the HK cohort included 552 594 new-onset hypertension patients and 2 548 914 controls. Hypertension was associated with increased CVD and mortality risks, which decreased with older onset ages. In the UK cohort, hypertension onset at ≤39 years had the highest risks for CVD and deaths, with adjusted hazard ratios (HR = 4.30, 95% CI [3.98, 4.65] and HR = 2.86, 95% CI [2.64, 3.10]). For patients with hypertension onset at ≥80 years, risks were lower, with adjusted HR = 2.56, 95% CI [2.45, 2.68] for CVD and HR = 1.11, 95% CI [1.09, 1.14] for deaths. Similar trends were observed in the HK cohort. Conclusion: Younger age of hypertension onset is associated with higher risks for cardiovascular events and mortality, highlighting the need for early screening and intensive interventions in younger adults to improve long-term blood pressure control and reduce cardiovascular complications and deaths, alleviating the chronic disease burden on the public healthcare system over the long term.